2015
DOI: 10.1038/ncomms8956
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: An apoptosis-enhancing drug overcomes platinum resistance in a tumour-initiating subpopulation of ovarian cancer

Abstract: High-grade serous ovarian cancers (HGSCs) are deadly malignancies that relapse despite carboplatin chemotherapy. Here we show that 16 independent primary HGSC samples contain a CA125-negative population enriched for carboplatin-resistant cancer initiating cells. Transcriptome analysis reveals upregulation of homologous recombination DNA repair and anti-apoptotic signals in this population. While treatment with carboplatin enriches for CA125-negative cells, co-treatment with carboplatin and birinapant eliminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 59 publications
8
49
0
Order By: Relevance
“…And vice versa, autophagy is able to be a promising target for further cancer treatment. Apoptosis, a process of programmed cell death, has been targeted to overcome platinum resistance through enhancing its function in ovarian cancer [12]. Therefore, in our study, after investigation of patients with gastric cancer in a clinical cohort, we aimed to suppress APE1 expression to induce apoptosis and autophagy by using its inhibitor AT101 in vitro , leading to find out a novel therapeutic target for gastric cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…And vice versa, autophagy is able to be a promising target for further cancer treatment. Apoptosis, a process of programmed cell death, has been targeted to overcome platinum resistance through enhancing its function in ovarian cancer [12]. Therefore, in our study, after investigation of patients with gastric cancer in a clinical cohort, we aimed to suppress APE1 expression to induce apoptosis and autophagy by using its inhibitor AT101 in vitro , leading to find out a novel therapeutic target for gastric cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A transcriptome analysis of ovarian cancer recently revealed that carboplatin-resistant high-grade serous ovarian cancer (HGSC) showed the up-regulation of anti-apoptotic signals as well as DNA repair signals [9]. The clinical samples examined in that study were obtained from CA125-negative HGSC cells, which are poorly differentiated and have similar features to CSC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, severe toxicities and drug resistance often occur, reducing the quality of life for patients and hindering the effective application of these agents (Chen et al, 2013, Janzen et al, 2015, Jayson et al, 2014, Yap et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been made in evaluating several classes of conventional chemotherapeutic agents, such as paclitaxel and platinum-based agents, for ovarian cancer therapy (Yap et al, 2009). However, the response rates are low, and clinical improvement is marginal, especially for patients with advanced stages of disease, largely due to late diagnoses, persistent dormancy, drug resistance, and cytotoxic side effects (Chen et al, 2013, Janzen et al, 2015, Yap et al, 2009). Therefore, it is necessary to develop new therapeutic agents for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%